Kenya : First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waivers and Modification of Performance Criteria; Staff Report; Press Release. (IMF Staff Country Reports; Country Report ;, 2011)
Based on the economic development and policies of Kenya, the staff report was prepared. GDP growth was broadly supported by both private and public investment. Policy issues related to monetary tightening to reign in inflationary expectations, medium-term, monitoring and emerging financial risks and gradual fiscal consolidation are discussed. A waiver for the nonobservance of the performance criteria on net domestic asset (NDA) and net international reserves (NIR) is outlined. A comprehensive public financial management at both the central and county government levels was introduced as a structural reform.